2018
DOI: 10.1186/s12864-018-4981-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of miRNAs in the gills of the mud crab (Scylla paramamosain) in response to a sudden drop in salinity

Abstract: BackgroundThe mud crab (Scylla paramamosain) is a euryhaline and commercially important species. MiRNAs participate in the regulation of many physiological activities.ResultsThe miRNA transcriptome of the gills of S. paramamosain was used to investigate the expression profiles of miRNAs in response to a sudden drop in salinity. In total, seven known miRNAs and 43 novel miRNAs were identified, with 18 differentially expressed small RNAs. Fourteen thousand nine hundred fifty-one differentially expressed miRNAs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 56 publications
(62 reference statements)
2
24
1
Order By: Relevance
“…The miRNA sequencing pipelines yielded 10,387,853 and 9,687,351 clean reads in the experimental and control groups, respectively (Table 1). Consistent with most previous results [2022, 2426], the majority of the sequences were distributed in the 21–22 nt range (Fig. 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The miRNA sequencing pipelines yielded 10,387,853 and 9,687,351 clean reads in the experimental and control groups, respectively (Table 1). Consistent with most previous results [2022, 2426], the majority of the sequences were distributed in the 21–22 nt range (Fig. 1).…”
Section: Discussionsupporting
confidence: 92%
“…With the developments of high-throughput sequencing technologies, a large number of miRNA transcriptome profiles have been obtained and characterized in various crustaceans, such as P. trituberculatus [21, 22, 27], E. sinensis [20, 23, 25], and S. paramamosain [24, 26, 28, 29]. Furthermore, miRNAs have been demonstrated to be vital for regulating gene expression and several biological functions, such as growth regulation [21], metabolism processes [22], and responses to viral infection [24].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a group of small non-coding RNAs, function as key post-transcriptional regulators of gene expression by complementary binding to 3′ untranslated regions of their target mRNA, leading to mRNA destabilization, or protein translation blockage ( 13 , 14 ). They are involved in many fundamental biological processes, such as development, metabolism, cell proliferation, and signal transduction ( 15 17 ). Recent evidence has revealed that miRNAs are critical in ovarian development and maturation in decapod crustaceans.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity is one of the most variable water quality factors (Chand et al., 2015) that can directly affect osmotic regulation (Setiarto, Strussmann, Takashima, Watanabe, & Yokota, 2015; Wang et al., 2018a, b; Wang, Wei, et al, 2019), hormone levels (cortisol) (Kiilerich, Kristiansen, & Madsen, 2007), and the immune and digestive enzyme activities (Wang & Chen, 2006) of aquatic organisms. Due to a stress response, aquatic animals will experience from internal physiological dysfunction, and their immune defence ability will be reduced (Gheisvandi, Hajimoradloo, Ghorbani, & Hoseinifar, 2015), thereby affecting their growth and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity is also one of the important environmental factors influencing overwintering in S. paramamosain (Zhen & Shao, 2001). S. paramamosain is a euryhaline crab (Wang, Tang, Wei, Lu, Mu, et al, 2018; Wang et al., 2018a, b; Wang, Wei, et al, 2019); however, previous studies on the effects of salinity on osmotic pressure, plasma cortisol, digestive, immunity and amino acid of crabs have mainly focused on a sharp change (Lu, Zhuang, Feng, Zhang, & Wang, 2011). However, there are few studies on the effects of long‐term gradual changes in salinity on S. paramamosain .…”
Section: Introductionmentioning
confidence: 99%